Bacterial biomass production in an estuarine system: high variability of leucine conversion factors and changes in bacterial community structure during incubation - Baptista, I. (2018)
Heterotrophic bacterioplankton play a key role in the transfer of organic carbon from the dissolved pool into planktonic trophic webs. The accurate measurement of bacterial biomass production (BBP) is crucial for the establishment of carbon budgets in aquatic systems. Estimation of BBP from the incorporation of radiolabelled leucine into bacterial proteins requires the use of empirical, semitheoretical or theoretical conversion factors (CFs). In this study, our estimate of the BBP for the estuarine system of Ria de Aveiro was higher when we used empirical and semitheoretical CFs than when we used theoretical ones. Empirical CFs ranged between 9.26 and 29.81 kg C mol–1 in the marine zone and between 4.25 and 16.88 kg C mol–1 in the brackish zone. Semitheoretical CFs ranged from 5.06 to 9.49 kg C mol–1 in the marine zone and from 5.28 to 9.34 kg C mol–1 in the brackish zone. During experiments to determine empirical CFs, the structure of the bacterial community was also analyzed. Sample preparation and the addition of leucine altered the structure of the bacterial community, and this probably affected the determination of the empirical CFs. The results show that, besides the effect of the use of an inadequate CF, the estimates of BBP can be biased in a system-specific way by the alteration of the structure of the bacterial community as a result of sample manipulation (i.e. filtration/dilution, incubation, and addition of non-radiolabelled and radiolabelled leucine).